The application of criminal sanctions against violations of cybercrime - Suleman Sulaeman (Indonesia Prime, 2017)
The era of globalization led to the more sophisticated information technology so that it has brought an impact on the emergence of various forms of crime which affect modern nature greater than the conventional crime. The crime using a computer since long ago is the type of crime that is difficult to classify as a criminal offence at one side of the technology can see as a means to achieve the goal. On the other hand, however, the technology can also be seen as a human activity.